Neonatal infections with multidrug-resistant ESBL-producing E. cloacae and K. pneumoniae in Neonatal Units of two different Hospitals in Antananarivo, Madagascar. Issue 1 (December 2016) - Naas, T.; Cuzon, G.; Robinson, A.; Andrianirina, Z.; Imbert, P.; Ratsima, E.; Ranosiarisoa, Z.; Nordmann, P.; Raymond, J.
Abstract Background We investigated the molecular mechanism of ß-lactam resistance in extended-spectrum ß-lactamase (ESBL)-producing Enterobacterial strains isolated in neonatal units of different hospitals in Anatnanarivo, Madagascar. Methods Bacteria were identified by standard biochemical methods, disc diffusion antibiograms and Etest. Resistance genes were sought by PCR. Strains were characterized by Rep-PCR (Diversilab), plasmid analysis and rep-typing. Results From April 2012 to March 2013, 29 ESBL-producingE. cloacae and 15 K. pneumoniae were isolated from blood culture (n  = 32) or gastric samples (n  = 12) performed at day 0 or 2 from 39/303 newborns suspected of early neonatal infection. These infants were treated with expanded spectrum cephalosporins, due to lack of carbapenems, leading to a high mortality rate (45 %). Isolates recovered were all, but 4, multidrug resistant, particularly to fluoroquinolones (FQ) except for 21E. cloacae isolates. Isolates produced TEM-1 and CTX-M-15 ß-lactamases and their genes were located on several self-transferable plasmids of variable sizes sizes that could not be linked to a major plasmid incompatibility group.E. cloacae isolates belonged to 6 Rep-types among which two counted for 11 isolates each. The FQ resistantE. cloacae isolates belonged to one clone, whereas the FQ susceptibleE. cloacae isolates belonged to four clones. TheK. pneumoniae isolates belonged to 9 Rep-types among which one included five isolates. Conclusion This study is the first molecular characterization of ESBL-producing isolates from neonatology units in Madagascar, a country with limited epidemiological data. It revealed an important multi-clonal dissemination of CTX-M-15-producing isolates reflecting both the high community carriage and the very early nosocomial contamination of the neonates.